Social Media Instagram Effect to Increase Brand Awareness on Dessert Industry - Siska, Julia; Rachmawati Chaldun, Evy (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract Dessert has become a trend for culinary connoisseurs in the year 2017. The success of dessert trend because the high users of social media Instagram. Social media Instagram is where the users can easily participate, sharing, and create the content themselves. Many business use these social media as a tool to promote their products and make customers aware with their brand. On the other hand, not all that business success to market their products. The purpose of this research is to find out the correlation between social media instagram effect to increase  brand awareness on dessert industry. Data was collected through questionnaire by using purposive sampling method. This research type which is explain the relationship between variable x and variable y. A total of 304 respondent’s data have been collected and analyzed using Multi linear Regression. The results show that there are significant correlation between independent variables (online community, interaction, sharing of content, accessibility, credibility, and trust) towards the dependent variable (brand awareness). This study is important for business owners because it can help to increase brand awareness in customer’s. Business owners can also make improvements and strengthen marketing channels based on selected variable to be more competitive. Keywords: Brand Awareness, Dessert Industry, Marketing Channel, Social Media Instagram, Trend.